PERFORMANCE STUDY AND EXPERIMENTAL CYCLES OF TWO STAGE SOLAR HYBRID ADSORPTION REFRIGERATION SYSTEM (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The performance parameters and experimental cycles of a solar adsorption refrigeration system working with the activated carbon-methanol working pair are presented here. Such a system has been fabricated and tested under the conditions of National Institute of Technology Calicut, Kerala, India. The performance parameters such as specific cooling power (SCP), coefficient of performance (COP), solar heating COP, solar cooling COP, uptake efficiency and exergy efficiency are studied. The dependency between the exergy efficiency and cycle COP with the driving heat source temperature for two thermal compressors is also studied. The optimum heat source temperature for the thermal compressor one is determined as 71.4oC and for the other thermal compressor it is 68.20C. The system has a mean cycle COP of 0.196 during day time and 0.335 for night time. The mean SCP values during day time and night time are 47.83 and 68.2, respectively. Experimental results also demonstrate that the adsorption refrigerator has cooling capacity of 47 to 78 W during day time and 57.6 W to 104.4W during night time. This study also presents the analysis of experimental thermodynamic cycle of solar adsorption refrigeration system. Two cycles have been analysed experimentally, one with clear sky and the other with partly cloudy. Use of artificial neural network model is proposed in order to predict the performance of the system. After training, it was found that LM algorithm with 9 neurons is most suitable for modeling solar adsorption refrigeration system. The ANN predictions of performance parameters are in good agreement with the experimental values with R2 values close to one and maximum percentage of error less than 5%. The RMS and covariance values are also found to be within the acceptable limits.